The review identifies evidence based practices for children, youth, and young adults with autism spectrum disorders, but research consumers should examine original studies. Issue 3 (1st October 2016) - Cook, Bryan G.; Cook, Sara E. C.
Abstract : This review provides a summary and appraisal commentary on the treatment review by Wong, C., Odom, S. L., Hume, K. A., Cox, A. W., Fettig, A., Kucharczyk, S., Brock, M. E. … Schultz, T. R. (2015). Evidence-based practices for children, youth, and young adults with Autism Spectrum Disorder: A comprehensive review. Journal of Autism and Development Disorders, 45, 1951–1966. doi: 10.1007/s10803–014-2351-z Source of funding and declaration of interests: This work was supported by the10.13039/100007296 US Office of Special Education Programs [grant number10.13039/100007296 H325G07004 ];10.13039/100005246 Institute of Education Science [grant number10.13039/100005246 R324B090005 ].